Integrative dynamics of cell wall architecture and plant growth under salt stress - Tariq, Faheem; Ma, Changle; Zhao, Shuangshuang (Frontiers in Plant Science, 2025)
Salt stress is a major challenge to agricultural productivity and can adversely affect plant growth and development. This review examines the interaction between cell wall architecture and plant tolerance to salt stress, focusing on the mechanisms underlying growth, remodeling, and anisotropic morphogenesis. It further elucidates how the cell wall’s composition, structure, and mechanical properties affect osmotic balance, ion transport, and physiological responses to salinity in plants. Key strategies for adaptation to stress, including the synthesis of osmoprotectants and alterations in cell wall polysaccharides, are discussed to understand their role in cell integrity and expansion under salt conditions. In addition, the review emphasizes the dynamic remodeling of the cell wall, which promotes anisotropic growth patterns necessary to maintain plant structure and function under environmental stresses. Based on the current research, this review highlights potential pathways to enhance plant adaptation to salinity through targeted manipulation of cell wall properties, providing insights for future biotechnological applications to improve crop performance in a saline environment.